Formulation of B2B Strategies for Steel Structure Product at a Construction Company in Domestic Market - Nuraisyah, Ani (Emerging Advances in Integrated Technology, 2025)
The company that will be discussed is one of those engaged in Indonesia’s construction industry. Because demand in foreign markets has decreased, this construction company is currently moving its target market to the domestic market with its main product in the form of steel structures. Based on sales data, the profit margin tends to be very small when compared to the increase in sales volume. The purpose of this study is to identify the main causes of the low annual profit of steel structure products in the domestic market and to formulate appropriate alternative strategies based on the company’s condition. The methods used in this study were Porter’s five forces, paired comparison, IFE, EFE, IE, SWOT, and QSPM. The results of the analysis show that the cause of the low annual profit of steel structure products is intense competition in the industry and the strong bargaining power of buyers. The SWOT matrix produces five alternative strategies, which are synthesized into three strategies, and in order of priority based on the QSPM matrix, the price adjustment strategy, the expanding market share strategy, and lastly, the maintaining loyalty strategy.